Creative Therapy and Economic Empowerment for People with Mental Disabilities through Eco-Print: A Community-Based Rehabilitation Model - Trenggono Pujo Sakti; Noning Verawati; Budhi Waskito (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Mental health recovery requires approaches that extend beyond clinical services by integrating psychosocial support, community engagement, and economic empowerment. Individuals in the recovery process continue to face social stigma, limited access to inclusive rehabilitation services, and barriers to social and economic reintegration. Pesantren possess social capital and cultural legitimacy that position them as potential settings for community-based rehabilitation. Purpose of the Study: This community service program aimed to enhance psychosocial functioning, creative capacity, social participation, and economic readiness among post-rehabilitation santri at Pondok Pesantren Jolo Sutro, Central Lampung, through eco-print–based creative therapy. Methods: The program employed a community-based rehabilitation approach implemented through five sequential mentoring phases, including initial assessment, introduction to creative activities, eco-print practice, process reflection, and sustainability strengthening. Evaluation was conducted using a performance-based assessment rubric to assess technical and psychosocial outcomes. Results: The assessment results showed scores ranging from 3 to 5, with a mean score of 4.0. Two indicators reached the highly proficient category, four indicators were classified as developing proficiency, and two indicators fell under basic emerging skills. These findings indicate consistent progress toward moderate to high levels of creativity and ecoprint technical mastery. The program was also associated with strengthened personal capacity, improved emotional regulation, enhanced social interaction, and the initiation of a pesantren-based eco-print business unit.